KINETIC INVESTIGATION OF PROPANE DISAPPEARANCE AND PROPENE FORMATION IN PROPANE OXIDATION ON DILUTED AND LEACHED MoVTeNb CATALYST - Restu Kartiko Widi (Universitas Gadjah Mada, 2010)
Reaction kinetics for the oxidation of propane over diluted-leached MoVTeNb is described. This paper is focused on the study of products selectivity profile and determination of the orders of propane disappearance and propene formation. The result shows that selective oxidation of propane to propene over this catalyst follows the Langmuir-Hinshelwood mechanism. The disappearance of propane is first order with respect to hydrocarbon and partial order (0.21) with respect to oxygen. The propene formation is first order with respect to hydrocarbon and not depending on oxygen concentration.